Semantic Analysis in The Short Story: The Gift of The Magi - Amelia Permata; Desy Nurmelia Putri; Divya Azzahra Putri Bahar; Lulu Izdihar Salsabila (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research aimed to analyze the short story “The Gift of the Magi” by O. Henry by examining the field of semantic studies, which focused on analyzing the existence of sentences, utterances, and presuppositions. This study focused on interpreting the meaning of sentences, utterances, and presuppositions in the short story “The Gift of the Magi,” as well as understanding the meaning of the purpose of each semantic analysis in the short story. The purpose of this study was to add insight into how to analyze a short story and interpret the meaning of a sentence, utterance, and presupposition that contributed to the narrative of the short story. The result of this research used a descriptive qualitative method in taking and analyzing data. This research used several theories from experts to interpret the data through sentence, utterance, and presupposition. This analysis showed that the story's narrative is shaped by both what is said and how it is said in context.